Experimental Infection of Human Volunteers with Haemophilus ducreyi: Fifteen Years of Clinical Data and Experience - Janowicz, Diane M.; Ofner, Susan; Katz, Barry P.; Spinola, Stanley M. (The Journal of infectious diseases, 2009)
Haemophilus ducreyi causes chancroid, which facilitates transmission of human immunodeficiency virus type 1. To better understand the biology of H. ducreyi we developed a human inoculation model. In the present article, we describe clinical outcomes for 267 volunteers who were infected with H. ducreyi. There was a relationship between papule formation and estimated delivered dose. The outcome (either pustule formation or resolution) of infected sites for a given subject was not independent; the most important determinants of pustule formation were sex and host effects. When 41 subjects were infected a second time, their outcomes segregated toward their initial outcome, confirming the host effect. Subjects with pustules developed local symptoms that required withdrawal from the study after a mean of 8.6 days. There were 191 volunteers who had tissue biopsy performed, 173 of whom were available for follow-up analysis; 28 (16.2%) of these developed hypertrophic scars, but the model was otherwise safe. Mutant-parent trials confirmed key features in H. ducreyi pathogenesis, and the model has provided an opportunity to study differential human susceptibility to a bacterial infection